Improving the safety of heparin usage by standardisation of practice - Eng Soo Yap; Pak Ling Lui; Su Ching Tan; Pik Wei Goh; Bhuvaneshwari Mohankumar; Peter Min Tun Ye; Kit Ching Tin; Winnie Z Y Teo (BMJ Open Quality)
Heparin, a high alert anticoagulant medication, is commonly used in medical settings in preventing and treating thrombotic events. However, its administration carries inherent risks for medication errors, bleeding complications and variability in practice standards across healthcare settings. This quality improvement project highlights the importance of standardising heparin administration practices and adopting a culture of adherence to best practices to improve patient safety and outcomes.